Anterior Urethral Valve: Uncommon Association with Renal Duplicity - Amina Ben Salem; Ines Mazhoud; Rachida Laamiri; Randa Salem; Hayet Laajili; Chiraz Hafsa (EL-Med-Pub, 2017)
Anterior urethral valves (AUVs) is an unusual cause of congenital obstruction of the male urethra, being 15-30 times less common than posterior urethral valves. We present a case of AUV diagnosed at 24th gestational week. Ultrasonography and fetal MRI revealed hydronephrotic kidneys with ureteral duplicity, a distended bladder and perineal cystic mass which confirmed dilated anterior urethra in a male fetus. Diagnosis was confirmed postnatally by voiding cystourethrogram and surgery.